Fundamental Investigations to Evaluate the Influence of Notching Processes on a Subsequent Cyclic Bending Process for the Production of Wire Cores - Biallas, Alina; Ohmayer, Sophia; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2023)
The production of wire cores by notch rolling and cyclic bending promises an ecologically and economically efficient manufacturing option for steel fibers. The paper at hand evaluates the influence of wire strips on cyclic bending by applying rolled wire strips of DP600 sheet metal (t0 = 0.8 mm) and a new cyclic bending testing tool. Analysis of material separation with varying parameters, rolling gap d and bending angle β, proves the interdependency of both process step, but indicates reduced adjustability of the notch rolling process. To enable better adjustability of the wire strip’s characteristics and analysis of their effects, wire strip production in the laboratory by notch stamping instead of rolling is aspired. The prior interaction analysis states the web height b, the notch angle α, and the hardening distribution as relevant wire strip’s characteristics to be replicated. Based on experimental analysis, an equivalent of notch rolling by notch stamping is deduced by considering the web height b identical for stamping and rolling, by adjusting the tool’s notch angle αt based on an equation considering geometric evaluations of α, and by taking advantage of the asymmetric hardening distribution of the outer notch which is comparable to rolled wire stri
Keywords: stamping; rolling; wire strip